2014
DOI: 10.17795/semj21869
|View full text |Cite
|
Sign up to set email alerts
|

Quality Evaluation of Educational Services Gap in Neyshabur Faculty of Medical Sciences Based on Service Quality Scale

Abstract: Background:Recognition of views and expectations of students is an important issue to improve the quality of educational services in the universities. Objectives: The aim of this study was to evaluatethe quality gap of educational services by using Service Quality (SERVQUAL) instrument in Neyshabur Faculty of Medical Sciences in viewpoints of students. Materials and Methods:In this cross-sectional study, data were collected using SERVQUAL instrument which comprisedof two questionnaires (perception and expectat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 6 publications
4
8
0
Order By: Relevance
“…Therefore, it appears that educational services in all aspects need to be reviewed and reformed. Similar studies in other Iranian medical universities so far have reported a negative gap in all dimensions (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). In a metaanalysis review conducted in 2019 using the SERVQUAL assessment model for the student satisfaction in Iranian medical universities, there was a negative gap in all five dimensions.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Therefore, it appears that educational services in all aspects need to be reviewed and reformed. Similar studies in other Iranian medical universities so far have reported a negative gap in all dimensions (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). In a metaanalysis review conducted in 2019 using the SERVQUAL assessment model for the student satisfaction in Iranian medical universities, there was a negative gap in all five dimensions.…”
Section: Discussionsupporting
confidence: 78%
“…By defining the gap in quality of services, programs can be developed for promoting the quality of education (2). The results of several studies conducted among the Iranian medical students showed that there is a gap in all five dimensions of quality of educational services (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Similar studies carried out among some universities outside Iran have also reported a gap in all dimensions (22)(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found the largest gaps in responsibility (22,23) and reliability (24,25). In contrast, some studies found the smallest gap in responsibility (26) and reliability (27). This dissimilarity can be caused by those different characteristics of patients, different facilities of health organizations, and the diverse nature of services.…”
Section: Discussionmentioning
confidence: 92%
“…In the observable and consistent dimensions, respectively, the largest and least negative quality gap means were found. There were substantial differences between beliefs and expectations of students in all dimensions represented by SERVQUAL [6].…”
Section: Discussionmentioning
confidence: 89%
“…In addition, because of its essential role in educating the community, medical education is of paramount importance today, requiring it to be continuously reviewed and remedied to address its shortcomings [5]. Because resource scarcity has always been a major obstacle to the implementation of quality programs, service quality assessment enables management to better allocate the limited financial resources available to better manage the organization while preventing quality loss [6]. Improve in areas that have the greatest impact on customer perception and expectation of service quality [7].…”
Section: Introductionmentioning
confidence: 99%